Biophysical analysis of the interaction of the serum protein human β2GPI with bacterial lipopolysaccharide. Issue 1 (2nd May 2014) - Gries, Anna; Prassl, Ruth; Fukuoka, Satoshi; Rössle, Manfred; Kaconis, Yani; Heinbockel, Lena; Gutsmann, Thomas; Brandenburg, Klaus
Abstract : There are several human serum proteins for which no clear role is yet known. Among these is the abundant serum protein beta2‐glycoprotein‐I (β2 GPI), which is known to bind to negatively charged phospholipids as well as to bacterial lipopolysaccharides (LPS), and was therefore proposed to play a role in the immune response. To understand the details of these interactions, a biophysical analysis of the binding of β2 GPI to LPS and phosphatidylserine (PS) was performed. The data indicate only a moderate tendency of the protein (1) to influence the LPS‐induced cytokine production in vitro, (2) to react exothermally with LPS in a non‐saturable way, and (3) to change its local microenvironment upon LPS association. Additionally, we found that the protein binds more strongly to phosphatidylserine (PS) than to LPS. Furthermore, β2 GPI converts the LPS bilayer aggregates into a stronger multilamellar form, and reduces the fluidity of the hydrocarbon moiety of LPS due to a rigidification of the acyl chains. From these data it can be concluded that β2 GPI plays a role as an immune‐modulating agent, but there is much less evidence for a role in immune defense against bacterial toxins such as LPS. Abstract : β2 ‐GPI binds more strongly to negatively charged phospatidylserine than to bacterial lipopolysaccharides (LPS). β2 ‐GPI has only a moderate tendency to influence LPS‐induced cytokine production in vitro . β2 ‐GPI reacts exothermally with LPS in a non‐saturable way. β2 ‐GPI changes its local microenvironment upon LPS association. The serum protein β2 ‐GPI is an immune‐modulating compound.